'Nonsense From the Beginning' — Allied Intervention in Russia's Civil War at 100: Historical Perspectives from Combatant Countries. Issue 4 (2nd October 2019) - Flake, Lincoln
ABSTRACT: To mark the hundredth anniversary of the often misunderstood Allied intervention in Russia's Civil War, The Journal of Slavic Military Studies has dedicated a section of this volume to assessing the impact of that convoluted operation. Lincoln Flake, a book review editor for the journal, introduces the topic. He is followed by contributions from five leading scholars from combatant nations. They provide unique insights into the desperate operations that occurred across Russia a century ago and the political and social consequences that followed.